Exploring Perspective of Local Tourists About City Branding: Study on Gorontalo As Serambi Madinah and Manokwari As Kota Injil - Juniarti, Gita; Sulistijowati, Rieny; Thomas, Abdul Wahab; Rosidi, Moh. Imron (Jurnal Bina Praja, 2023)
City branding is an object contested by various cities and regencies in Indonesia. The goal was to introduce their identity of them, so strong branding could be the basis for marketing tourism from the city. Therefore, the purpose of this study was to examine the perspectives of domestic tourists about city branding that use religion as the basis for their branding. This study analyzes the perspectives of tourists who visit Gorontalo City and Manokwari Regency. Gorontalo has the branding Serambi Madinah, and Manokwari is famous with Kota Injil as its branding. This study uses a qualitative approach and descriptive analysis based on Tourism Consumption Behavior (TCB) and critical questions for developing a city brand strategy. This study was conducted in 19 days, from 1 February to 20 February 2023, by interviewing tourists who visited Gorontalo City and Manokwari Regency. Literature studies also support the discussion in this study. The results showed that Gorontalo City, which has Serambi Madinah branding, has not attracted tourists' attention to sites, mosques, and religious festivals held in Gorontalo City. Tourists prefer to travel to the coast of Tomini Bay, such as Pulo Cinta and Botubarani Whale Sharks. Meanwhile, tourists visiting Manokwari have a more perspective that Manokwari is Kota Injil, where the bible first entered Papua through Manokwari. Several factors can also influence city branding: local history, culture, natural resources, and religion. Local wisdom is also essential to support the city's branding.